THE INFORMATION TECHNOLOGY REVOLUTION IN ORAL SURGERY - Juan Rapheal Diaz Simoes; Rashidi Sarah (Educational Research in Universal Sciences, 2023)
The field of oral surgery has undergone a significant transformation in recent years, driven by the rapid advancement of information technology (IT). This article explores the various ways in which IT is revolutionizing oral surgery, from diagnosis and treatment planning to surgery and post-operative care. It discusses specific technologies such as 3D printing, artificial intelligence (AI), and virtual reality (VR) and their impact on patient care. Additionally, the article highlights the ethical considerations surrounding the use of IT in oral surgery and the need for data security and patient privacy.